Molecular-scale dynamics of light-induced spin cross-over in a two-dimensional layer - Kaushik Bairagi (Nature Portfolio, 2016)
Spin crossover molecules may find applications in ultimately small magnetic devices, given the sensitivity of their spin-states to external stimuli. Here, the authors show a light-induced transition between two ordered dynamic phases in two-dimensional spin crossover layers on a metallic surface.